DNA module platform for developing colorimetric aptamer sensors. (June 2016) - Tomita, Yasuyuki; Morita, Yuji; Suga, Hiroaki; Fujiwara, Daisuke
Here we present a DNA module platform for developing simple aptamer sensors based on a microarray format combined with secondary structure prediction in silico. The platform comprises four parts: ( i ) aptamer, ( ii ) joint module, ( iii ) terminal stem, and ( iv ) a DNAzyme that catalyzes a redox reaction controlled by a structural change induced by aptamer/target binding. First, we developed a joint module, capable of sensing a conformational change in the aptamer region, that was linked to the signal transmission activity of a DNAzyme as the reporter in a concentration-dependent manner with the AMP aptamer. This module design was then used to generate an arginine sensor simply by replacing the AMP aptamer region with a previously reported arginine aptamer. Using this DNA module platform, we were also able to customize a microarray containing >10, 000 sequences designed by in silico secondary structure prediction and successfully identify a new aptamer against patulin. Our results show that the DNA module platform can be used to readily devise sensors based on known aptamers as well as create new aptamer sensors by array-based screening.